Analysis of Rasch Model for the Validation of Chemistry National Exam Instruments - Ayi Darmana; Ani Sutiani; Haqqi Annazili Nasution; Ismanisa Ismanisa*; Nurhaswinda Nurhaswinda (Universitas Syiah Kuala, 2021)
Information about score obtained from a test is often interpreted as an indicator of the student's ability level. This is one of the weaknesses of classical analysis that are unable to provide meaningful and fair information. The acquisition of the same score if it comes from a test item with a different level of difficulty, must show different abilities. Analysis of the Rasch model will overcome this weakness. The purpose of this study was to analyze the quality of the items by validating the national chemistry exam instrument using the Rasch model. The research sample was 212 new students of the Department of Chemistry at the State University of Medan. The data collected was in the form of respondent's answer data to the 2013 chemistry UN questions, which amounted to 40 items multiple choice and uses the documentation method. Data analysis technique used the Rasch Model with Ministep software. The results of the analysis show the quality of the Chemistry National Exam (UN) questions is categorized as very good based on the following aspects: unidimension, item fit test, person map item, difficulty test level, person and item reliability. There is one item found to be gender bias, in which men benefit more than women. The average chemistry ability of respondents is above the average level of difficulty of the test items